KEBIJAKAN POLITIK KEUANGAN TERHADAP PEMBANGUNAN NEGARA DALAM SISTEM KETATANEGARAAN ISLAM - Muhammad Syahwalan (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstract: Islam has practically taught people about the income-politics policies employed by Prophet Muhammad SAW from the previous period. Zakat has been well-known as one of the state income concept. Zakat is globally a part of 5 (five) pillars of Islam, besides shadat, prayer, fasting, and hajj. One form of responsibility is to maintain finance income and expenditure. One of the things that will be an interesting improvement in this article is about the method of income and budget spending in order to carry out state activities to achieve the goal of prosperity for the society. The results of the study are zakat, ghanimah, fai ', jizya, and kharaj / tax. The revenue from the sources of funds obtained is allocated to public interests such as poverty eradication, state defense and security, legal development, development of infrastructure and social facilities, and education.Keywords: Income;  Expenditur; tax; policy.